2016
DOI: 10.18666/jasm-2016-v8-i4-7263
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Outbound Ticket Sales: Examining Social Media Strategies Among Top-Performing Salespeople

Abstract: This paper examines current implementation of social media strategies by ticket salespeople. A sample of 126 ticket sales professionals across professional, collegiate, and minor league sport responded to a survey measuring social media usage rates across a variety of platforms, social media use throughout the sales process, and sales performance. Results indicate that overall ticket salespeople are not incorporating social media into their regular sales initiatives. However, topperforming sales professionals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Courses already on the books with titles like marketing, promotion, public relations sponsorship, fundraising, communication, finance, and management could be used as a vehicle to deliver sales content and allow students to demonstrate certain sales competencies. For example, Warren (2016) found that top-performing salespeople use social selling significantly more than those who do not.…”
Section: Sales Competencies Across the Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…Courses already on the books with titles like marketing, promotion, public relations sponsorship, fundraising, communication, finance, and management could be used as a vehicle to deliver sales content and allow students to demonstrate certain sales competencies. For example, Warren (2016) found that top-performing salespeople use social selling significantly more than those who do not.…”
Section: Sales Competencies Across the Curriculummentioning
confidence: 99%
“…These signs include the development of a body of scholarly literature in sport sales. Academic scholarship has investigated sales management practices (Popp et al, 2017;Wanless & Judge, 2014), factors influencing sales effectiveness (Pierce, Lee, & Petersen, 2014); social selling practices (Warren, 2016), and the development of a competency model (Pierce & Irwin, 2016). All of the previous factors provided fertile ground for the first academic textbook devoted to teaching students how to sell within the sport industry .…”
Section: Introductionmentioning
confidence: 99%
“…The current study agrees with much of the existing literature surrounding box office operations and their effect on sport ticket sales. Previous studies have shown box office operations as impactful on customer satisfaction (Smith & Roy, 2011) as well as pricing (Warren, 2016) and word-of-mouth behavior (Theodorakis & Alexandris, 2008). Where the current study contributes to the box office operations literature lies in the specific measurement of individual aspects of the sales process, and how each specifically predicts purchase behavior, giving a more detailed view of the sales process and sales effectiveness surrounding box office operations.…”
Section: Theoretical Implicationsmentioning
confidence: 90%
“…Theodorakis and Alexandris (2008) In a more recent study, Warren (2016) studied the impact of ticket sales using social media as a platform to develop a relationship between the sales representative and the customer. Warren (2016) posited social media selling can benefit the sales representative throughout the sales process, allowing for personal communication and the discovery of customer needs in a way which was less intrusive than the "cold call" concerns identified by Theodorakis and Alexandris (2008). Warren (2016) found the social media platform LinkedIn was the most popular method of active social selling, though social media was used scarcely across of sport for sales purposes.…”
Section: Box Office Influence On Consumer Behaviormentioning
confidence: 99%
See 1 more Smart Citation